For two goods $x$ and $y$, the elasticity of substitution is defined as $$\sigma \equiv \frac{d\log\left(\frac{y}{x}\right)}{ d\log\left(\frac{U_x}{U_y}\right) }= \frac{\frac{d\left(\frac{y}{x}\right)}{\frac{y}{x}}}{ \frac{d\left(\frac{U_x}{U_y}\right)}{\frac{U_x}{U_y}}} $$

I am confused by two things:

  1. Why do we just write $d\log\left(\frac{y}{x}\right)$? What are we differentiating with respect to?
  2. How do I use that that to show the above relation?

Can someone explain?


1 Answer 1


How to derive elasticity of substitution

The first step is to recall the definition of a differential. If you have a function $f: \Bbb R^n \to \Bbb R$, say, $f(x_1,\cdots,x_n)$, then: $${\rm d}f = \frac{\partial f}{\partial x_1}{\rm d}x_1 + \cdots + \frac{\partial f}{\partial x_n}\,{\rm d}x_n. $$

For example, $$d\log v = \frac{1}{v}dv$$

Now suppose $v = \tfrac{y}{x}$, then we have $$ d\log(y/x)=\frac{d(y/x)}{(y/x)}$$

and for $v = \tfrac{U_x}{U_y}$

$$ d\log(U_x/U_y)=\frac{d(U_x/U_y)}{(U_x/U_y)}$$

In other words, if you reduce the problem to (1) understanding the definition of a differential and (2) use a simple change of variable, the problem becomes very straightforward.

You then get

$$\sigma \equiv \frac{d\log\left(\frac{y}{x}\right)}{ d\log\left(\frac{U_x}{U_y}\right) }= \frac{ \frac{d(y/x)}{(y/x)} }{ \frac{d(U_x/U_y)}{(U_x/U_y)} } $$


Note, it is important to recognize that $ d(y/x)$ is a meaningful concept. You simply apply quotient rule and you find

$$ d(y/x)= \frac{xdy-ydx}{x^2}$$

This makes sense because

$$ d\log(y/x) = d\log(y) - d\log(x) = \frac{dy}{y}-\frac{dx}{x}$$

And if you compute

$$ d\log(y/x)=\frac{d(y/x)}{(y/x)}=\frac{ \frac{xdy-ydx}{x^2}}{y/x} = \frac{xdy-ydx}{xy} = \frac{dy}{y}-\frac{dx}{x}$$

Same logic applies to $d(U_x/U_y)$.

Thus, all of $\sigma$ is well-defined in the sense we are using the calculus tools correctly / legally.

What is elasticity of substitution?

Elasticity is by how much % one thing changes relative to a % change in another. Therefore, in this case, it is % change in ratio of two goods relative to a single % change in the $MRS$ for those two goods.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.